2015
DOI: 10.1021/acs.jced.5b00610
|View full text |Cite
|
Sign up to set email alerts
|

Reference Quality Vapor–Liquid Equilibrium Data for the Binary Systems Methane + Ethane, + Propane, + Butane, and + 2-Methylpropane, at Temperatures from (203 to 273) K and Pressures to 9 MPa

Abstract: A specialized cell designed for vapor liquid equilibrium (VLE) measurements at cryogenic temperatures and high pressures was used to measure new (p,T,x,y) data for binary mixtures of methane + ethane, + propane, + 2-methylpropane (isobutane), and + butane from (203 to 273) K at pressures up to 9 MPa. A literature review of VLE data for these binary mixtures indicates that a significant number have large uncertainties; however, because estimates of uncertainties in measured phase compositions are often not quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 36 publications
1
39
0
1
Order By: Relevance
“…These recommended sets, along with the present data and those of May et al [29] are plotted in red in figure 6; there is much better internal consistency between these sets compared to the literature data overall.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…These recommended sets, along with the present data and those of May et al [29] are plotted in red in figure 6; there is much better internal consistency between these sets compared to the literature data overall.…”
Section: Resultssupporting
confidence: 62%
“…Dr. Eric Lemmon of NIST [23] made his database of mixture data available to us, and it included five additional sources not referenced by Kunz et al (these were Kalra and Robinson [24], Powers et al [25], Cutler [26], Roof and Baron [27], and Stoeckli and Stateley [28]). The only recent source was that of May et al [29] In total, there are 21 literature sources with 787 data points at saturation; these cover the full range of composition and temperatures spanning nearly the full range from the triple point to critical point of propane (85.5 K to 369.9 K). Most of the sources report VLE (typically ( p, T, x ) or ( p, T, x, y )) data, and in figure 6, we plot deviations in the saturation pressure (either bubble-point pressure or dew-point pressure, depending on what was reported).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syringe Pump Volume Measurement 0.01 cm The mole fraction of methane in the liquid phase, x 1 , was estimated via a flash calculation using the GERG-2008 EOS as implemented in REFPROP, from the measured temperature, pressure and overall mixture composition. For binary mixtures of methane + propane, May et al 14 showed recently that the root mean squared (r.m.s.) deviation between liquid phase methane mole fraction measured over the temperature range from (203 to 283) K at pressures to 8 MPa and those calculated with the GERG-2008 EOS was 0.0087.…”
Section: B Proceduresmentioning
confidence: 99%
“…The work by Haniff and Pearce 12 used laser-light scattering to determine the surface tension while approaching the critical temperature for one mixture (z 1 =0.62, z 2 = 0.38) across the range T = (302.75 to 312.35) K. The phase compositions and densities for the surface tension calculation presented by Weinaug and Katz 9 and Haniff and Pearce 12 were derived from the phase equilibrium data of Sage et al 13 . There has been substantial improvement since the work done by Sage et al 13 , in the accuracy with which the phase compositions and densities of the methane + propane system can be described 14 . Thereby it should be possible to significantly improve upon the description of the system's surface tension as determined by these authors, and in addition, continue those surface tension measurements up to the critical point.…”
Section: Introductionmentioning
confidence: 99%